2021
DOI: 10.1051/e3sconf/202123701010
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Rhizosphere Soil Microbial Community Structure Associated with Five Land Use Types in Jinchuan Mining Area

Abstract: Five different land use types (desert, farmland, mining park, slag heap and tailing dam) were selected as variables around the Jinchuan Cu-Ni mining area in Jinchang, Gansu Province in the present study. The Atriplex canescens (Pursh) Nutt.’s rhizosphere bacterial abundance, diversity and community composition were examined taking advantage of High-throughput sequencing technology to discuss the effect of soil physicochemical properties on soil microbial community structure. The result indicated that the phylu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Zarraonaindia et al reported that both vegetation types and soil types affected soil microbial communities [ 12 ]. Gao et al found soil environmental factors significantly affected the diversity of microbial community composition [ 13 ]. Xue et al showed that land use type significantly affected the biomass, diversity and composition of soil microbes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zarraonaindia et al reported that both vegetation types and soil types affected soil microbial communities [ 12 ]. Gao et al found soil environmental factors significantly affected the diversity of microbial community composition [ 13 ]. Xue et al showed that land use type significantly affected the biomass, diversity and composition of soil microbes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%